Abonos orgánicos y su influencia en el rendimiento de forraje de Panicum máximum cultivar tanzania en Zungarococha - Loreto. 2022 - Bocanegra Vasquez, Juan Diego (2022)
The fertilizers of different species of animals in the production of forage are an area that the National University of the Peruvian Amazon in the Faculty of Agronomy, located in the Loreto region, the research work has the title: ORGANIC FERTILIZERS AND ITS INFLUENCE ON FORAGE YIELD OF Panicum maximum CULTIVAR TANZANIA IN ZUNGAROCOCHA – LORETO. 2022. With a Random Complete Block Design (D.B.C.A), with four treatments and four repetitions, the treatments under study were: T1(20 tons of poultry manure/ha), T2(20 tons of poultry manure/ha), T3 (20 tons of sow) and T4 (20 tons of cows/ha), leaving the respective data: plant height of 103.05 centimeters, green matter of 3.58 kg/m2 and dry matter of 0.79 kg/m2, coverage of 90.75 percent and the leaf: stem ratio, all this with a time of 60 days from the start of sowing. The yield variable, if we compare from highest to lowest, treatment T1 (20 tons of chicken manure/ha) with 35,800 kilos, second place T3 (20 tons of sow) with 28,800 kg./ha, third place treatment T2 (20 tons of chicken manure) with 25,000 kg. and fourth place was T4 (20 tons of Bovinaza/ha) with 23,500 kg. all this in green matter per hectare 60 days after sowing.